Early complications after esophageal atresia repair: analysis of a German health insurance database covering a population of 8 million. Issue 7 (20th April 2015) - Dingemann, C.; Dietrich, J.; Zeidler, J.; Blaser, J.; Gosemann, J.‐H.; Ure, B. M.; Lacher, M.
Abstract : Summary: The treatment of esophageal atresia is not centralized in Germany. Therefore, high numbers of departments are involved. Data on the results of esophageal atresia repair from Germany are lacking. The aim of this study was to evaluate the early postoperative results after repair of esophageal atresia based on unbiased data of a German health insurance. We aimed to determine whether characteristics of the departments had an impact on outcome and compared the results from this study with the literature data from centers with a high caseload. Data of a German health insurance covering ∼10% of the population were analyzed. All patients who had undergone esophageal atresia repair from January 2007 to August 2012 were included. Follow‐up data of 1 year postoperatively were analyzed. The potential impact of various characteristics of the treating surgical institutions was assessed. Results were compared with the latest international literature. Seventy‐five patients with esophageal atresia underwent reconstructive surgery in 37 departments. The incidences of anastomotic leak (3%) and recurrent tracheoesophageal fistula (7%) were comparable with the literature (both 2–8%). Anastomotic stricture required dilatation in 57% of patients (mean 5.1 ± 5.6 dilatations) comparing unfavorably to most, but not all international reports. During 1‐year follow‐up, 93% of the patients were readmitted at least once (mean 3.9 ± 3.1 admissions). The incidence of complications did not correlate with any of the characteristics of the treating institutions such as academic affiliation, the number of consultants, beds, and preterm infants treated per year (all P > 0.05). Based on unbiased data, postoperative results after repair of esophageal atresia in Germany are comparable with recently published reports from international single centers. A correlation between the complication rate and characteristics of the treating institutions was not identified.